STRATEGI KEBIJAKAN SEKTOR PERTANIAN DALAM MENDUKUNG PENINGKATAN INDEKS KETAHANAN PANGAN PADA ASPEK KETERSEDIAAN PANGAN DI PROVINSI KEPULAUAN RIAU - Kawasi, Brian (BUANA SAINS, 2025)
The aim of this research was to analyze the effectiveness of agricultural sector policies in improving the Food Security Index (IKP), particularly in terms of availability, in the Riau Islands Province, which is one of the provinces with the lowest IKP in Indonesia. The study employed a mixed-methods approach with a descriptive-analytical design. Primary data were collected through a structured questionnaire administered to 25 experts and policymakers in the food and agriculture sector. Secondary data were obtained from Bapanas and BPS. Data analysis was conducted using a scoring technique (1-10) for six policy alternatives based on the criteria of effectiveness, efficiency, and long-term impact, followed by an Avoid-Shift-Improve (ASI) analysis. The scoring results showed that the market access improvement policy achieved the highest score (110), followed by food reserve strengthening (106). The ASI analysis indicated that all policies fell into the improve category, with food reserve strengthening having the highest Improvement score (9). Key findings revealed that the root cause of low food availability is an extreme dependence on imports (exceeding 90% for some commodities) and a weak distribution infrastructure. This research provides empirical evidence of measurable policy priorities for the island context. Its strategic recommendation is to integrate strengthening distribution logistics (market access) with optimizing community-based food reserves as a short-term measure, while encouraging technology-based local food diversification in the long term.